Arabic language learning plays a significant role in fostering cross-cultural communication, especially in Muslim-majority countries like Indonesia. One of the critical language skills that receive attention is writing (?????rah), which serves as a foundatio: Implementasi strategi pembelajaran maharotul kitabah pada dauroh bahasa arab kelas X Aliah di pondok pesantren Al-Ittifaqiah - Ilda Sagita Ilda (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2024)
Arabic language learning plays a significant role in fostering cross-cultural communication, especially in Muslim-majority countries like Indonesia. One of the critical language skills that receive attention is writing (?????rah), which serves as a foundation for mastering the language productively. However, teaching Arabic writing skills often faces challenges, particularly in pesantren-based educational institutions with a dense curriculum and limited resources. A major challenge identified is the low motivation among students to develop their writing skills, often struggling with grammar and expressing ideas in writing. This study aimed to analyze the implementation of Arabic writing learning strategies at Pondok Pesantren Al-Ittifaqiah, focusing on 10th-grade students. The research utilized a qualitative descriptive approach, gathering data through interviews, classroom observations, and curriculum document analysis. Findings revealed that contextual learning approaches, which incorporate real-life scenarios, significantly engaged students in writing tasks. The study also identified the supportive learning environment, such as the availability of Arabic reference books and a strong literacy culture, as factors enhancing learning. Despite these positive factors, the study highlighted challenges, including limited teaching methods and time constraints for writing practice. In conclusion, to improve Arabic writing skills, pesantren administrators should encourage innovative teaching methods and allocate more time for writing practice, while also training educators to adopt more varied and contextual approaches. Keywords: Arabic writing, contextual learning, pesantren, teaching strategies, student motivati on